Effects of air to fuel ratio on parameters of combustor used for gas turbine engines: Applications of turbojet, turbofan, turboprop and turboshaft - Aygun, Hakan (Pergamon-Elsevier Science Ltd, 2024)
Combustors of gas turbine engines have generally the highest irreversibility due to the combustion process. Therefore, to observe influence of air to fuel ratio (AFR) on combustor performance is of high importance. In this study, thermodynamic laws are employed to separately determine adiabatic flame temperature (AFT), entropy production, exergy destruction and exergy efficiency of combustor for turbojet (TJ), turbofan (TF), turboprop (TP) and turboshaft (TS) where variables are AFR, combustor inlet temperature (CIT) and combustor pressure ratio (CPR). In this regard, the higher the AFR, the lower the adiabatic flame temperature, however the higher the entropy production for related combustor. Similarly, increasing AFR leads to raise exergy destruction, thereby lowering exergy efficiency. On the other hand, as CIT increases, exergy efficiency of the combustor improves whereas slight effects of CPR on the combustor metrics are observed. Namely, due to variation of AFR, exergy destruction of combustor changes between 0.512 MW and 0.825 MW for TJ, between 1.807 MW and 2.735 MW for TS, between 28.38 MW and 40.49 MW for TF and between 3.102 MW and 4.564 MW for TP. Moreover, exergy efficiency of combustor changes between 59% and 73% for TJ, between 70% and 77% for TS, between 78% and 81% for TF and between 75% and 79% for TP engine through the determined AFR and CIT ranges. These findings indicate that combustor of each gas turbine engine demonstrates different behavior according to the mentioned variables and exergy efficiency of combustor depends on finding the optimum points of combustor variables.
Keywords: Combustor; Air to fuel ratio; Exergy efficiency; Adiabatic flame temperature